In situ Kerr and harmonic measurement in determining current-induced effective fields in MgO/CoFeB/Ta - Wong, Qi Ying (2021)
A combination of the harmonic measurement and in situ Kerr imaging was used to experimentally determine the spin-orbit (SO) effective fields in a MgO/CoFeB/Ta structure. Here, we evaluate the SO effective fields through an analytical energy approach by transforming the anomalous Hall effect and planar Hall effect (PHE) voltage into a field dependency while imaging the magnetisation behaviour by differential Kerr microscopy. The analytical fitting to the measurement data indicates the significant coexistence of both a transverse field, HT, and longitudinal field, HL, in the longitudinal (H L = -12 Oe, H T = 8 Oe per 106 A cm-2) and transverse (H L = -12 Oe, H T = -17 Oe per 106 A cm-2) measurement schemes, respectively, due to the PHE. Additionally, dendritic-like domains, indicating the influence of the interfacial Dzyaloshinskii-Moriya interaction (DMI) at the CoFeB/Ta interface, were observed by in situ Kerr imaging. Micromagnetic simulations confirm the dendritic domain formation and edge tilting of the magnetisation, as being due to the DMI.